Soil solarization as a substitute for methyl bromide fumigation in greenhouse tomato production in Cyprus - Ioannou, Nicolas (My University, 2000)
Preplant soil fumigation with methyl bromide (MB) is presently standard practice in greenhouse tomato production. Since this compound is scheduled to be phased out by 2005, the possibility of using solarization as an alternative soil disinfestation method was examined in four greenhouse tomato trials. Solarization was applied for 8 weeks in July-August, using transparent polyethylene sheets for soil mulching, and compared with MB fumigation applied in September, before planting, at 80 g/m2. Solarization raised the maximum soil temperature by 9°C and reduced the population density of Fusarium spp. in soil by 91-98%. Similar reductions of soil inoculum (95-99%) were obtained with MB fumigation. Both methods provided effective control of Fusarium wilt, Verticillium wilt and corky root rot on tomato plants. MB fumigation was in addition highly effective against root-knot nematodes, whereas nematode control with solarization did not exceed 50%. Both treatments resulted in similar fruit yield increases, ranging within 90-140% compared with plants grown in untreated soil. During the second cropping season following soil treatment, solarization exhibited two times higher residual effectiveness against vascular wilt diseases compared with MB fumigation. The latter treatment, however, was superior to solarization in its residual effectiveness against root-knot nematodes and to a lesser extent against corky root rot. Fruit yields from solarized and MB-fumigated soil during the second cropping season were higher than those obtained from untreated soil by approximately 35% and 60%, respectively. In Cyprus, solarization appears to be an effective alternative to MB fumigation in greenhouse tomato production, especially if integrated with other approaches enabling more effective nematode control.
Keywords: Corky root rot; Fusarium wilt; Lycopersicon esculentum; Meloidogyne spp; Pyrenochaeta lycopersici; Root-knot nematodes; Verticillium wilt